Status and influencing factors of balance in middle-aged and older adults with Parkinson’s disease: a national longitudinal study - Wu-xiao Wei; Xin-gui Zhuo; Hong-qiao Chen; Ming-li Chen (Frontiers in Neurology)
BackgroundTo examine the current status and influencing factors of balance in middle-aged and older adults with Parkinson’s disease (PD) and explore the correlations of these factors with balance.MethodsThe China Health and Retirement Longitudinal Study (CHARLS) Database in 2015, 2018 and 2020 were utilized as the data source, from which the missing value samples were excluded and 1,390 participants aged ≥45 years were recruited. Using the chi-square test, balance comparisons were made among middle-aged and older adults PD patients under different indicators. The influences of different factors on the patient balance were investigated through regression analysis.ResultsRegression analysis revealed the correlations of age, gender, smoking, falls, hypertension, diabetes and physical activity with balance in PD patients. A significant association between aging and declined balance was found, with middle-aged and older adults PD patients aged > 65 years showing a higher probability of declined balance (OR = 0.716, p = 0.016). Male middle-aged and older adults PD patients exhibited better balance than female counterparts (OR = 1.829, p = 0.001). Previous smoking (OR = 0.580, p = 0.004), falls (OR = 0.769, p = 0.035), hypertension (OR = 0.738, p = 0.019) and diabetes (OR = 0.734, p = 0.027) were positively correlated with the declined balance in PD patients. Light physical activity could significantly improve balance in middle-aged and older adults PD patients (OR = 1.672, p < 0.001).ConclusionBalance impairment is a major concern for middle-aged and older adults with PD. Our findings highlight that age, gender, smoking, history of falls, hypertension, diabetes, and physical activity significantly influence balance. Specifically, old age, male gender, light physical activity (such as walking), and lower risks of hypertension and diabetes are linked to better balance. Clinicians should focus on managing these risk factors and promoting light physical activity to improve balance and reduce fall risks.